2004
DOI: 10.1124/jpet.104.071027
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Improves Spatial Learning in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: Memantine, a low-to moderate-affinity uncompetitive N-methyl-D-aspartate receptor antagonist, has been shown to improve learning and memory in several pharmacological models of Alzheimer's disease (AD). In the present study, the effect of memantine on locomotor activity, social behavior, and spatial learning was assessed in a transgenic mouse model of AD. Eight-month-old male C57BL/6J mice carrying mutated human APP and PS1 genes (APP/PS1) and their nontransgenic (NT) litter mates were administered a therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
124
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 44 publications
9
124
1
Order By: Relevance
“…We were surprised to find no effect of memantine on contextual memory in a fear conditioning paradigm given that we used doses similar to those previously been reported to have beneficial behavioral effects in other transgenic mouse models of AD (Minkeviciene et al, 2004;Van Dam et al, 2005;Van Dam and De Deyn, 2006). The behavior deficits we observed in Tg + mice replicated earlier findings using Tg2576 mice (Hsiao et al, 1996;Corcoran et al, 2002;Arendash et al, 2004;Barnes and Good, 2005;Dong et al, 2005) and thus imply validity of the behavioral test employed here.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We were surprised to find no effect of memantine on contextual memory in a fear conditioning paradigm given that we used doses similar to those previously been reported to have beneficial behavioral effects in other transgenic mouse models of AD (Minkeviciene et al, 2004;Van Dam et al, 2005;Van Dam and De Deyn, 2006). The behavior deficits we observed in Tg + mice replicated earlier findings using Tg2576 mice (Hsiao et al, 1996;Corcoran et al, 2002;Arendash et al, 2004;Barnes and Good, 2005;Dong et al, 2005) and thus imply validity of the behavioral test employed here.…”
Section: Discussionsupporting
confidence: 71%
“…We selected three doses (5, 10, and 20 mg/ kg) for this study in an attempt to approach the therapeutic doses typically used in humans Parsons, 2003, Wenk et al, 2006). Previous studies in mice have reported that a 30 mg/kg oral dose of memantine in drinking water produces a steady-state plasma drug level of around 1 mM, which is thought to be therapeutic based on clinical studies (Kornhuber and Quack, 1995;Minkeviciene et al, 2004). However, it is difficult to select drug doses in animal studies that are equivalent to clinical doses because the composition and responses observed in the brains of rodents and humans differ (Wenk et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Memantine treatment (30 mg/kg/day p.o.) for 2 to 3 weeks initiated at the age of 8 months also significantly improved the acquisition of the Morris Water Maze in APP/PS1 mice AD model without affecting swimming speed although it had no effects on locomotor activity or aggressive behaviour (Minkeviciene et al 2004).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 95%